Corrupted: A Game to Teach Programming Concepts. - Chau, Brian; Robinson, Adam; Pace, Jason; Nash, Rob; Sung, Kelvin (Computer (00189162), 2014)
Collaborative teams at the University of Washington Bothell are designing games like Corrupted that introduce students to basic programming structures and functionalities.